PENGUATAN BRAND IDENTITY DAN DIGITAL MARKETING UNTUK PENINGKATAN DAYA SAING USAHA ANEKA KERIPIK DAN PEYEK LAS YAYANG - Irfan Hassandi; Yossinomita; Mardiana R.; Eni Rohaini; Saifan Ali Fazila; Amilia Difa S. Putri (LPPM ITB AAS Indonesia Surakarta, 2026)
This community service activity aims to strengthen brand identity and enhance digital marketing skills for the MSME Aneka Keripik and Peyek Las Yayang in Jambi City. The main issues faced by the partner are the weak brand identity and the limited use of digital media for promotion. The program was conducted using a participatory approach through counseling, training, and direct mentoring on brand management concepts, visual identity design, and social media–based digital marketing strategies. Evaluation through pre- and post-tests revealed a significant improvement in participants’ understanding of brand identity, digital marketing strategies, and the use of social media for online sales. This activity had a positive impact on raising awareness among MSME actors about the importance of branding and digital technology utilization to expand markets and strengthen business competitiveness.